Developmental stages of a common grass yellow butterfly, Eurema hecabe - Arju, M Hasina; Miah, Md Kowser; Parven, Nousheen; Bashar, MA (Dhaka University Journal of Biological Sciences, 2015)
Developmental stages of pierid butterfly (Lepidoptera: Pieridae) Eurema hecabe, duration and survival rate of developmental stages was studied in laboratory condition under 29 ± 3ºC temperature with RH 78 ± 2%. Egg, five larval instars and pupal stage were distinct. The average duration from egg to adult, incubation period, larval and pupal period was recorded 22.0 ± 0.7, 5.7 ± 6, 10.5 ± 0.4 and 6.5 ± 0.4 days, respectively. Twenty seven out of 34 larvae were successfully completed their whole 5 instars. Positive correlation among the larval instars, amount of food consumption and excretion of faeces were observed. About 65% pupae emerged as adult at laboratory condition. Dhaka Univ. J. Biol. Sci. 24(1): 73-81, 2015 (January)